Methods for suspension culture, protoplast extraction, and transformation of high‐biomass yielding perennial grass Arundo donax. Issue 12 (28th November 2016) - Pigna, Gaia; Dhillon, Taniya; Dlugosz, Elizabeth M.; Yuan, Joshua S.; Gorman, Connor; Morandini, Piero; Lenaghan, Scott C.; Stewart, C. Neal
Abstract: Arundo donax L. is a promising biofuel feedstock in the Mediterranean region. Despite considerable interest in its genetic improvement, Arundo tissue culture and transformation remains arduous. The authors developed methodologies for cell‐ and tissue culture and genetic engineering in Arundo . A media screen was conducted, and a suspension culture was established using callus induced from stem axillary bud explants. DBAP medium, containing 9 µM 2, 4‐D and 4.4 µM BAP, was found to be the most effective medium among those tested for inducing cell suspension cultures, which resulted in a five‐fold increase in tissue mass over 14 days. In contrast, CIM medium containing 13 µM 2, 4‐D, resulted in just a 1.4‐fold increase in mass over the same period. Optimized suspension cultures were superior to previously‐described solidified medium‐based callus culture methods for tissue mass increase. Suspension cultures proved to be very effective for subsequent protoplast isolation. Protoplast electroporation resulted in a 3.3 ± 1.5% transformation efficiency. A dual fluorescent reporter gene vector enabled the direct comparison of the CAMV 35S promoter with the switchgrass ubi2 promoter in single cells of Arundo . The switchgrass ubi2 promoter resulted in noticeably higher reporter gene expression compared with that conferred by the 35S promoter in Arundo . Abstract : Arundo donax, giant reed, is a very large grass that grows in the Mediterranean region. The auhtors developed methodologies for biotechnological improvements of giant reed that resulted in novel cell‐ and tissue cultures needed to enable genetic engineering of the crop. The auhtors demonstrated the utility of various genetic elements in genetically engineered cells to establish a platform technology for future practical improvements of giant reed for bioenergy applications.